Legal Review of Consumer Dispute Settlement in Cases of Cancelled Property Development : Study Decision Number : 072/ Arbitration /2022/ BPSK.Mdn - Andreas Marfel Silaban; Beby Sendy (International Journal of Law and Society, 2025)
Consumer dispute resolution in Indonesia is an increasingly relevant issue, considering the high dynamics of transactions that occur in the goods and services sector, including in the property sector. Consumers, as the weaker party in business transactions, often face problems related to the quality of goods/services received, delays, unilateral cancellations, or even failure in property development. Therefore, resolving consumer disputes is very important and requires adequate legal protection. This type of research is normative juridical research. Normative research is literature research by examining theoretical approaches and concepts that examine consumer disputes. Normative juridical research is legal research that places law as a building system of norms. Problems arise when consumers in good faith have paid all Down Payment obligations, but the business actor actually takes a unilateral decision to cancel the apartment construction project. Consumers who have invested funds amounting to IDR 307,530,900 are trying to get a refund, but the business actor does not show responsiveness and good faith in the refund process. This situation finally forced consumers to take legal action by filing a lawsuit with BPSK Medan City on December 5 2022. This case is a clear example of the application of consumer protection and the importance of BPSK as an alternative for resolving disputes outside of court. This decision also reflects the principles of justice and legal certainty in consumer disputes, where agreed consumers can obtain their rights through an arbitration mechanism.